(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Congenital fetal anomalies are an important causes of neonatal morbidity and mortality in developed and developing countries that affect health care system. Knowledge of maternal sociodemographic and antenatal characteristics could identify a pattern of population at risk in order to target preventive interventions. The study aimed to determine the pattern of congenital anomalies in newborns, as well as the associated maternal characteristics at a tertiary level hospital in Dhaka and Chattogram, Bangladesh. Materials and methods: A descriptive cross-sectional study was conducted at Combined Military Hospital, Dhaka and Chattogram between February 2023 to September 2023, February 2021 to September 2021. A total of 50 pregnant women with fetal congenital anomalies admitted to the Department of Obstetrics and Gynaecology were included in this study. Pattern of anomalies and maternal sociodemographic and antenatal characteristics were recorded in a proforma. Results: The mean age of the mother was 27.3±6.4 years. Twenty seven (54%) of the baby were male and 23 were female (gender ratio 1.2:1). More common congenital anomalies were hydrocephalus (26%), anencephaly (22%), cleft lip (6%), cleft lip & palate (6%), polydactyly (6%), and hydrops fetalis (6%). Associated materanl characteristics were high maternal age (34%), consanguinity of marriage (14%), maternal under-nutrition (22%), maternal obesity (6%), exposure to drugs (10%), associated medical conditions (34%), no history of folic acid intake in antenatal period (62%), high grade fever in 1st trimester and history of previous birth defect (8%). Conclusion: Congenital anomalies of the CNS and musculoskeletal or gastrointestinal defects were seen most frequently. More research is required to identify the factors responsible for the different types of congenital anomalies. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 47-51